1989
DOI: 10.1093/carcin/10.12.2279
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of metallothionein in CHO cells and its effect on cell killing by ionizing radiation and alkylating agents

Abstract: Metallothionein protein protects cells from the toxic effects of heavy metal ions. To establish its protective function against ionizing radiation and alkylating agents, a model system was created by transfecting two CHO cell lines (wild-type, K1-2 and X-ray sensitive, xrs-2 subclone Bc11) with the human metallothionein II-A (hMTII-A) gene integrated in a bovine papilloma derived autonomously replicating vector. The isolated transfectants are cadmium-resistant (Cdr), due to the overexpression of the hMTII-A ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The protein plays a protective role, preventing against intoxication with heavy metals, such as Pb, Hg, Cu, Cd [8,9]. MT manifests also a strong anti-oxidative activity, protecting cells from the damaging effects of reactive oxygen species, ionizing radiation and chemotherapeutic agents [10][11][12]. Intensely dividing cells (including tumor cells) manifest an increased expression of MT, which supplies zinc (Zn) ions for enzymes involved in DNA replication and protects cells from apoptosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…The protein plays a protective role, preventing against intoxication with heavy metals, such as Pb, Hg, Cu, Cd [8,9]. MT manifests also a strong anti-oxidative activity, protecting cells from the damaging effects of reactive oxygen species, ionizing radiation and chemotherapeutic agents [10][11][12]. Intensely dividing cells (including tumor cells) manifest an increased expression of MT, which supplies zinc (Zn) ions for enzymes involved in DNA replication and protects cells from apoptosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…3) In addition, MT appears to promote the resistance of cells to not only some alkylating agents and chemotherapeutic metal compounds, such as cisplatin, chlorambucil and melphalan, 4) but also electrophilic mutagens such as N-methyl-N′-nitro-N-nitrosoguanidine and N-methyl-N-nitrosourea. 5) Interestingly, MT has also been implicated in protection against the cytotoxic effects of oxidative stress, because it is a potent hydroxyl radical scavenger. 6) In vitro, MT protects cells against the cytotoxic and DNA-damaging effects of nitric oxide and the DNA-damaging effects of H 2 O 2 , 7) and also against radical-induced lipid peroxidation.…”
mentioning
confidence: 99%
“…MTs are known to play putative roles in cancer cell proliferation and apoptosis (Abdel-Mageed and Agrawal, 1997;Jayasurya et al, 2000) as well as in resistance to radiation and chemotherapeutic agents (Lohrer and Robson, 1989;Yang et al, 1994, Kondo et al, 1995. In breast cancer, MT overexpression has been well documented by immunohistochemical analysis (Schmid et al, 1993;Fresno et al, 1993;Haerslev et al, 1995;Goulding et al, 1995;Jin et al, 1999), and shown to be predominantly associated with poor prognosis.…”
mentioning
confidence: 99%